Genetic influences of angiotensin-converting enzyme inhibitor response: an opportunity for personalizing therapy?. (August 2012) - Brugts, Jasper J; Simoons, Maarten L
The angiotensin-converting enzyme (ACE) inhibitors are a cornerstone drug therapy in the current treatment of patients with hypertension, stable coronary artery disease and heart failure. Individualizing therapy of ACE inhibitors with clinical risk factors in low-risk patients with stable coronary artery disease is not feasible. The concept of pharmacogenetics, by studying patient factors more individually, offers a first glimpse in the quest for the 'holy grail' of personalized medicine. As such, genetic targets in the direct pharmacodynamic pathway of ACE inhibitors, the renin–angiotensin–aldosterone system, is a plausible candidate for such an approach. In the past few decades, results of pharmacogenetic studies were scarce and inconsistent. However, recently the first reports of larger pharmacogenetic studies are now confirming that the 'pharmacogenetic approach' might be feasible in the future. The current review focuses on the recent developments in pharmacogenetic research in response to ACE inhibitors in patients with stable coronary artery disease.